Effect of ultrasound on the enhancement of biodegradability: a study with olive mill wastewaters - Çoker, H. Sertan. (Thesis (M.S.)-Bogazici University. Institute of Environmental Sciences, 2009., 2009)
Olive mill wastes are a significant source of potential or existing environmental pollution in the Mediterranean region. The environmental impacts of olive mill wastewaters are considerable with the dangerous effects such as colouring of natural waters, threat to the aquatic life, causing surface and groundwater pollution, changing soil quality and plant growth. In this research, the removal efficiencies of organic matter and the biodegradability enhancement in the treatment of olive mill wastewaters via applying Ultrasound, UV irradiation, Fenton, photo-Fenton and combinations of them were investigated. The aim of the study was to determine the most appropriate process and its operating conditions for the treatment of olive mill wastewaters using advanced oxidation methods. It was found that ultrasonic bath used in this study was ineffective to produce sufficient hydroxyl radicals for degradation of organic matter. However, the effectiveness of the bath increased when the system was combined with AOP processes like Fenton and UV irradiation either sequentially or simultaneously. The sequential processes of US/UV followed Fenton Process was determined the most effective method for treating olive mill wastewater in terms of COD, BOD5 removal and biodegradibility enhancement.
Keywords: Olive oil industry -- Waste disposal.; Olive oil -- Biodegradation.